Mean arterial pressure at the initiation of continuous renal replacement therapy as a prognostic indicator in patients with acute kidney injury - Haiying Song; Yuheng Liao; Haofei Hu; Qijun Wan (Renal Failure)
Background Acute kidney injury (AKI) is a common complication in critically ill patients, with approximately 5% requiring continuous renal replacement therapy (CRRT). This study investigated the relationship between mean arterial pressure (MAP) and 28- and 90-day mortality in critically ill AKI patients treated with CRRT.Methods This secondary analysis of a bicenter, retrospective, observational study included patients with AKI who were treated with CRRT from January 2009 to September 2016. Mortality at 28 and 90 days post-CRRT initiation was analyzed using multivariate regression, generalized additive models, smooth curve fitting, and sensitivity analyses.Results A total of 1,142 patients were included, with 28-day and 90-day mortality rates of 62.1% and 71.8%, respectively. In multivariable-adjusted Cox models, MAP was inversely correlated with the risk of 28-day and 90-day mortality after adjusting for covariates. Hazard ratios (HRs) were calculated per 1 mmHg increment of MAP: adjusted HR for 28-day mortality 0.985 (p < 0.00001) and for 90-day mortality 0.987 (p = 0.00002). The adjusted HRs for 28-day and 90-day mortality in patients in the highest tertile of MAP compared with those in the lowest tertile were 0.682 (95% CI 0.543–0.857) and 0.730 (95% CI 0.592–0.899), respectively. Patients were grouped using MAP thresholds of <65 mmHg, 65–71.85 mmHg, and ≥71.85 mmHg, with similar results observed. Sensitivity analyses confirmed the inverse relationship between higher MAP before CRRT and lower mortality.Conclusion The higher the MAP before CRRT is, the lower the 28- and 90-day mortality of critically ill patients with AKI who are treated with CRRT.